Evidence in contemporary civil procedure : fundamental issues in a comparative perspective / editors, C.H. van Rhee, A. Uzelac. - Rhee, C. H. van; Uzelac, Alan (Ius commune europaeum ;, 2015)
Since the start of the new millennium, many contemporary jurisdictions have been revisiting the fundamental principles of their civil procedures. Even the core areas of the civil process are not left untouched, including the way in which evidence is introduced, collected and presented in court. One generator of the reforms in the field of evidence-taking in recent decades has been slow and inefficient litigation. Both in Europe and globally, reaching a balance between the demands of factual accuracy and the need to adjudicate disputes in a swift, cost-effective and efficient way is still one of the key challenges. The second reason that many countries are reforming their law of evidence is related to cultural and technological changes in modern societies. As the balance between, on the one side, traditional human rights such as the right to privacy and due process is shifting towards, on the other side, the modern need for security, efficiency and quick access to justice, the perception of what is admissible or not in the context of evidence-taking is changing as well. In the same sense, the fast pace of modern life commands different practices of fact-finding, accompanied by new methods of selection of evidence that are appropriate for this purpose. Last but not least, the overwhelming penetration of new technologies into all spheres of public and private life has the capacity to dramatically change the methods of the collection and presentation of evidence.Exploring these issues, the editors of this book invited the contributors to reflect on how these trends affect the situation in their countries and to present their views on further developments, both nationally and in comparison with the developments in other countries and regions. A further goal was to inquire whether, in spite of national differences that are still dominant, the approaches to civil evidence are converging, and whether reforms affecting fact-finding have a chance of leading to some forms of harmonization.This publication has been produced with the financial support of the 2007-2013 Civil Justice Programme of the European Union. The contents of this publication are the sole responsibility of authors and can in no way be taken to reflect the views of the European Commission.